Corrigendum to "Saturation control of switched nonlinear systems" [Nonlinear Anal. Hybrid Syst. 32 (2019) 320–336]. (November 2019) - Zhang, Junfeng; Raïssi, Tarek
Abstract: A correction is provided for the paper "Saturation Control of Switched Nonlinear Systems" published in Nonlinear Anal. Hybrid Syst. 32 (2019) 320–336. The main correction includes that one inequality sign is modified and the last section of the proof of Theorem 1 is corrected.